The statistical evaluation of digestion methods for Myrtus Communis and Peganum Harmala (Comprehensive Journal of Science, 2025)
Element concentrations in two selected medicinal plants Myrtus Communis and Peganum Harmala have been determined using four digestion procedures for samples preparation. These elements include Ca, Mg, Na, K, Fe, P, Si, Mn, Zn, Cu, Co, Ni, Cr, Al, Hg, Pb and Cd which were identified using ICP-ES instrument. Regardless of the digestion methods, Ca, Mg, K, Na, P and Fe as macronutrients were presented in maximum quantities in these plants. Meanwhile, the highest level of micronutrients was recorded for Si, Mn and Zn respectively. The toxic element Al represents the highest concentration according to other toxic elements in medicinal plants selected for this study which could be referred to environmental composition.The statistical results exhibit a significant variation between water extraction procedure and other digestion procedures. This variation could be related to the ability of water to extract organic and inorganic salts only. In mean time, (HNO3/HClO4) digestion procedure has the superiority over there methods for sample preparations. The statistical data also exhibit significant variance according to the elemental composition. for instance, these herbs have significant differences in concentration of Mn, Cu, Cr, Zn, Sn and Si, meanwhile no significant variances were detected with the concentration of Co and Ni.